OPTIMALISASI TEKNOLOGI INFORMASI DI JURUSAN PEMASARAN SMK NEGERI 1 BANYUDONO - Roychan Ahda Abdillah; Jonet Ariyanto Nugroho; Leny Noviani (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
The purpose of this study was to find out the use, benefits and constraints of information technology in learning at the departement of Marketing at State Vocational High School 1 Banyudono. This study used a qualitative approach with a case study model. The sampling technique used is non probability purposive sampling with snowball sampling strategies. Data collection techniques used were in-depth interviews and documentation study with data analysis techniques interactive analysis Miles & Huberman. The results showed that the use of information technology in learning at the departement of Marketing at State Vocational High School 1 Banyudono still not optimal, that is merely a computer assisted learning, while other models such as: e-learning, blended learning and distance learning can’t yet be applied.